VARIAÇÃO SAZONAL DA CARAVELA Physalia physalis (LINNAEUS, 1758) EM PRAIAS URBANAS AMAZÔNICAS. - SILVA, Fabio de Almeida e (2018)
In the Amazonian urban beaches has been observed the occurrence of agglomerations of Portuguese man-of-war Physalia physalis) throughout the year. These organisms are known due to the numerous cases of accidents involving humans, mainly on the coast of the north and northeast regions of Brazil. The present study aimed to characterize the seasonal distribution of the Portuguese man-of-war and the interactions of abiotic factors in its agglomeration. The abundance data were obtained with fortnightly samplings by means of active search in the beaches during the years of 2005, 2006, 2007, 2012, 2013, 2015 and 2016. Each colony had its biometric data recorded for characterization regarding the presence of juveniles and adults. Abiotic data were obtained from a meteorological station near to the beaches, and the data set was analyzed using the statistical model of linear regression for the understanding of the agglomerations on the beaches. Finally, we conclude that the Portuguese man-of-war colonies are present throughout the year, and its seasonality is evidently marked by the occurrence of greater abundances in second half of the year, and the influence of the northeast trade winds. In addition, it is verified that part of the agglomerations is influenced by the several reproductive events that occur throughout the year.